Construction of solutions to PDEs using holomorphic functions of several variables - Shpakivskyi, Vitalii (Electronic journal of differential equations, 2024)
The work develops Humbert's method of solving PDEs. It applies method for constructing solutions of the three-dimensional  Laplace, Helmholtz, and Poisson equations in the form of components  of holomorphic functions of several variables (complex and hypercomplex). For more information see https://ejde.math.txstate.edu/Volumes/2024/71/abstr.html